ARGUMEN GOTTFRIED WILHELM LEIBNIZ TERHADAP PEMBUKTIAN EKSISTENSI TUHAN - Krisna Sukma Yogiswari (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2020)
Gottfried Wilhelm Leibniz is a German philosopher who provides a comprehensive argument about the existence of God. Although Leibniz has made a mistake in thinking about God, the evidence of God's existence offered by him gives us an example and a strength to deepen our faith: Leibniz's courage is to deepen his faith and his strength to maintain God's existence. Also it seems that with evidence of harmony that had been built before, Leibniz fell into the trap of atheism implicitly because it denied the existence of a personal God and only relied on internal law. Regarding harmony that had been built before, according to Leibniz there was an internal law that worked within the monade. monade so that monades are a natura that has been determined and consequently has only one nature: the nature that governs everything. But the best is that not only for the whole in general, but also for individuals especially especially individuals who have love for God.